Opportunities and challenges to implementing bird conservation on private lands. (19th April 2013) - Ciuzio, Elizabeth; Hohman, William L.; Martin, Brian; Smith, Mark D.; Stephens, Scott; Strong, Allan M.; Vercauteren, Tammy
Abstract With >70% of the United States held in private ownership, land‐use decisions of landowners will ultimately dictate the future of bird conservation in North America. However, land‐use objectives of landowners vary considerably and present opportunities and challenges for bird conservationists. Innovative strategies incorporating proactive approaches to address educational, financial, social, and economic needs of landowners are required to garner participation in conservation programs and practices to create or enhance bird habitat on privately owned working lands. Farm Bill conservation programs and practices provide unprecedented opportunities to facilitate bird conservation at regional and national scales and frequently serve as the primary vehicle for many non‐governmental organizations to accomplish their bird conservation goals. We identify current challenges and opportunities for bird conservation on private lands and present 4 case studies whereby partnerships with federal agencies, mainly the U.S. Department of Agriculture's Natural Resources Conservation Service, have proven successful in eliciting positive, measurable outcomes to bird conservation efforts on private lands spanning many North American physiographic regions. The future of bird conservation will increasingly rely upon the ability of federal agencies to prioritize and allocate additional resources to deliver bird conservation programs on private lands and a greater awareness by conservationists of the role of economics in the decision‐making process of landowners. © 2013 The Wildlife Society.